Bacillus Responses to Plant-Associated Fungal and Bacterial Communities - Andrić, Sofija; Meyer, Thibault; Ongena, Marc (Frontiers in Microbiology, 2020)
Some members of root-associated Bacillus species have been developed as biocontrol agents due to their contribution to plant protection by directly interfering with the growth of pathogens or by stimulating systemic resistance in their host. As rhizosphere-dwelling bacteria, these bacilli are surrounded and constantly interacting with other microbes via different types of communications. With this review, we provide an updated vision of the molecular and phenotypic responses of Bacillus upon sensing other rhizospheric microorganisms and/or their metabolites. We illustrate how Bacillus spp. may react by modulating the production of secondary metabolites such as cyclic lipopeptides or polyketides. On the other hand, some developmental processes such as biofilm formation, motility and sporulation may also be modified upon interaction, reflecting the adaptation of Bacillus multicellular communities to microbial competitors for preserving their ecological persistence. This review also points out the limited data available and a global lack of knowledge indicating that more research is needed in order to, not only better understand the ecology of bacilli in their natural soil niche but also to better assess and improve their promising biocontrol potential.